Enhancing VO₂Max Through Tabata-Based Sport Rhythm Training: An Experimental Study Among Students of Sports Coaching Education, Universitas Negeri Medan - Syahputra Manik; Agussalim Samosir; Ramlan Sahputera Sagala; Ghozi Indra Waskita; Ibrahim Ibrahim; Siti Rahima Gultom (Physical Activity Journal (PAJU), 2026)
This study aims to analyze the effectiveness of Tabata-based sport rhythm training in improving VO₂max among students of the Sports Coaching Education program at the Faculty of Sports Science, Universitas Negeri Medan. The study employed a quasi-experimental design using a pretest–posttest control group approach. The sample consisted of 30 students selected through random sampling, who were then divided into two groups: an experimental group and a control group. The instrument used to measure VO₂max was the Multistage Fitness Test (bleep test). The intervention was conducted over six weeks, with training sessions three times per week. Data were analyzed using paired sample t-tests and independent sample t-tests with a significance level of 0.05. The results indicated a significant improvement in VO₂max in the experimental group following the Tabata-based sport rhythm training intervention (p < 0.05). Furthermore, there was a significant difference between the experimental and control groups in the posttest results, demonstrating that the applied training method was more effective than conventional training. This improvement can be attributed to the characteristics of Tabata training, which combines high intensity with short intervals, thereby optimizing aerobic capacity. In conclusion, Tabata-based sport rhythm training is effective in improving VO₂max among students of Sports Coaching Education. This method can serve as an alternative training model to enhance cardiorespiratory fitness efficiently and systematically.